Al-Ghazali’s Ethical Paradigm and It’s Relevance in Aqidah-Akhlak Instruction at Islamic Boarding School Based Madrasah Aliyah Tarbiyatut Tholabah - Ratih Kusuma Ningtias; Miftahuddin; Ciska Fitria Adie (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2025)
In the context of contemporary education, many madrasahs attempted to integrate character education into their curriculum. The implementation of Al-Ghazali's thought into the Aqidah Akhlak curriculum at Madrasah Aliyah was expected to contribute positively to character education in Indonesia. This study did not only aim to examine the theory but also provided practical recommendations for educators and policymakers in designing a more effective curriculum. As stated by Raqib, in-depth research on the integration of Islamic values in education opened opportunities to improve the quality of education in a Muslim-majority country. This research used a literature review method by examining relevant sources related to curriculum concepts, character education, and Al-Ghazali's thought. In addition, document analysis of the operational curriculum of Madrasah Aliyah Tarbiyatut Tholabah was also conducted. The literature analysis became an effective method for collecting comprehensive information and providing a broader context to the issues studied. The results of the study showed that Al-Ghazali's perspective on curriculum had a significant impact on the development of the Aqidah Akhlak curriculum at Madrasah Aliyah Tarbiyatut Tholabah. Al-Ghazali's concept of ethics was not only relevant in shaping students' character but also in creating a more conducive learning environment. These findings indicated that the integration of moral values in education could improve the overall quality of education and prepare a generation that was not only intelligent but also possessed strong integrity.